2018
DOI: 10.1007/s11696-018-0490-y
|View full text |Cite
|
Sign up to set email alerts
|

The range of protein hydrolysis and biogenic amines content in selected acid- and rennet-curd cheeses

Abstract: The aim of this experiment was to assess the range of proteolysis and biogenic amine content in the selected rennet- and acid-curd cheeses available on the Polish market, randomly chosen for the analyses: three ripened hard with eyes cheeses, three ripened hard smooth cheeses, three ripened soft moulded cheeses, three fresh unripened acid-curd cheeses, three ripened acid-curd cheeses with slimming bacteria—fried, and three ripened acid-curd cheeses with smear bacteria. The results allowed calculating the subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 35 publications
(89 reference statements)
0
17
2
Order By: Relevance
“…Today, society is increasingly aware of the importance of diet for health, and hence, any issue relating to food safety has a considerable impact on consumer behavior and official policy [16]. Among fermented food products, cheese is most commonly related with biogenic amines (mostly histamine, tyramine, cadaverine, and putrescine) intoxication [34,35]. Recently, the EFSA (European Food Safety Authority) Panel on Biological Hazards (BIOHAZ) conducted a qualitative risk assessment for biogenic amines (BAs) in fermented foods, and concluded that our present knowledge of their toxicity was limited and that further research was needed [36,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, society is increasingly aware of the importance of diet for health, and hence, any issue relating to food safety has a considerable impact on consumer behavior and official policy [16]. Among fermented food products, cheese is most commonly related with biogenic amines (mostly histamine, tyramine, cadaverine, and putrescine) intoxication [34,35]. Recently, the EFSA (European Food Safety Authority) Panel on Biological Hazards (BIOHAZ) conducted a qualitative risk assessment for biogenic amines (BAs) in fermented foods, and concluded that our present knowledge of their toxicity was limited and that further research was needed [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Standarová et al [40] reported that Olomouc tvorogs contained, among other amines, the highest level of cadaverine, at up to 2413.00 mg/kg. According to Bonczar et al [35], this amine is predominant in Harzer cheese and can occur at the level of 377.50 mg/kg, and Fiechter et al [41] found this amine at the level of 1268.00 mg/kg in Harzer cheese. According to Andiç et al [22], the levels of cadaverine ranged from not detected to 1844.50 mg/kg in herby cheese.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, permitted levels for histamine (His) in unprocessed fish have been established at 100-200 mg kg −1 and up to 400 mg kg −1 in fish sauce, while there are not regulations set for dairy products [11]. HPLC with pre-column derivatisation and UV/VIS or photo-diode array detection (PAD) have served as the main methods for the analysis of BAs in mould cheeses [12][13][14]. A recent study, based on HPLC-MS/MS with cation exchange column, has shown advantages for the analysis of ten BAs, while avoiding the derivatisation step [15].…”
Section: Introductionmentioning
confidence: 99%
“…Biogenic amines have been found in Feta ( Valsamaki et al, 2000 ), Akawi cheese ( Pachlová et al, 2016 ), Beyaz peynir ( Durlu-Özkaya et al, 1999 ), Iranian white brined cheese ( Aliakbarlu et al, 2011 ; Rohani et al, 2013 ), and other varieties of white-brined cheeses and ripened cheeses collected from the European dairies and small-scale farms ( Bunkova et al, 2013 ; Combarros-Fuertes et al, 2016 ; Bonczar et al, 2018 ; Espinosa-Pesqueira et al, 2018 ; Mayer and Fiechter, 2018 ). Based on diverse research, EFSA published the mean values of histamine (21–62 mg/kg), tyramine (68–104 mg/kg), putrescine (25–65 mg/kg), and cadaverine (72–109 mg/kg) recorded in cheese ( EFSA, 2011 ).…”
Section: Properties and Spoilage Potential Of Yeastsmentioning
confidence: 99%